Penguatan Literasi Numerasi dan Berpikir Kritis Matematika Siswa di SMK Ma’arif NU Martapura - Maulida, Dina; Yanti, Williza; Fitria, Mia; Hidayat, Farid; Muslim, Azis; Ferita, Rolina Amriyanti; Khalizah, Ismi Ardiandari Nur; Dani, Ahmad (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
Students' lack of ability to answer questions that do not match the examples is the background for carrying out community service activities in addition to students' lack of motivation in learning. Students' fixation on examples causes students to have difficulty when given questions that are slightly different. There are several causes of students' difficulties in answering questions based on the results of analysis with the teacher, namely students' critical thinking abilities and students' numeracy literacy. These two abilities are the basis for students to solve problems using the information provided from the questions and concepts they have studied. This community service activity is carried out with the aim of providing stimulus to students to strengthen students' critical thinking and numeracy literacy skills. The stimulus is provided in the form of simple and non-routine questions using Pisa questions and questions related to third-dimensional material in the form of essays. Apart from that, it is also interspersed with math games to motivate students to learn.This activity was carried out at SMK Ma'arif NU Martapura.The results of the service show that there are five indicators of critical thinking skills and three indicators of numeracy literacy that are met. Apart from that, students also begin to have the courage to speak and show a positive attitude in learning. This can be a recommendation for teachers to provide more stimulus for non-routine questions so that students' critical thinking skills and numeracy literacy are further honed.